2010
DOI: 10.1136/ard.2010.134817
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: an instrumental factor in the anti-phospholipid syndrome by inhibition of tissue factor expression

Abstract: Vitamin D deficiency is common among APS patients and is associated with clinically defined thrombotic events. Vitamin D inhibits anti-β2GPI-mediated TF expression in vitro. Thus, vitamin D deficiency might be associated with decreased inhibition of TF expression and increased coagulation in APS. Evaluation of vitamin D status and vitamin D supplementation in APS patients should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 45 publications
2
99
0
7
Order By: Relevance
“…Additionally, experimental models suggest significant role of complement system and inflammation in APS pathogenesis, which is similar to SLE pathogenesis [49][50][51]. New data indicate role of vitamin D in SLE pathogenesis and also very current are researches of vitamin D role in APS [52]. Based on many similarities with SLE, some authors indicate possible systemic character of APS and raise an intriguing question: are http://www.mjms.mk/ http://www.id-press.eu/mjms/ APS and SLE two separate autoimmune disorders or represent one same autoimmune phenomenon?…”
Section: Is Antiphospholipid Syndrome a Systemic Autoimmune Disorder?mentioning
confidence: 89%
“…Additionally, experimental models suggest significant role of complement system and inflammation in APS pathogenesis, which is similar to SLE pathogenesis [49][50][51]. New data indicate role of vitamin D in SLE pathogenesis and also very current are researches of vitamin D role in APS [52]. Based on many similarities with SLE, some authors indicate possible systemic character of APS and raise an intriguing question: are http://www.mjms.mk/ http://www.id-press.eu/mjms/ APS and SLE two separate autoimmune disorders or represent one same autoimmune phenomenon?…”
Section: Is Antiphospholipid Syndrome a Systemic Autoimmune Disorder?mentioning
confidence: 89%
“…It was shown that ~ 50% of patients had vitamin D deficiency (<15ng/ml) which correlates with thrombotic complications and other clinical manifestations of the syndrome (neurological, ocular, livedo reticularis and skin ulcers). In vitro, vitamin D seems to suspend the anti-2GPI-induced expression of TF [ 67 ]. The role of anti-endothelial antibodies, especially of anti-HSP60, in the mechanism of thrombosis was studied in LA positive patients with secondary APS [ 68 ].…”
Section: Clinical and Laboratory Characteristicsmentioning
confidence: 99%
“…Numerous infectious agents have been related to autoimmunity and production of autoantibodies [20][21][22] as well as with evident diseases such as SLE and APS [23][24][25][26][27]. Additional factors such as hormones [28,29], vitamins such as vitamin D [30][31][32], sun exposure, etc. were also allied the pathogenesis of both SLE and APS [33].…”
mentioning
confidence: 99%